2021
DOI: 10.1111/idh.12556
|View full text |Cite
|
Sign up to set email alerts
|

Motivators and barriers to oral hygiene self‐care among adolescents in Malaysia: A qualitative study

Abstract: Oral health is a crucial component of general health and well-being.Having good oral health would impact positively on the overall health and quality of life. 1 Advocating the importance of good oral health should begin early in life as studies have shown that children and adolescents with good oral health would tend to develop healthy teeth in their adult life. 2,3 To achieve good oral health, having good oral hygiene practice is essential. Although oral diseases such as dental caries and gingivitis are preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In the present study, the oral health promotion facilitator was a dental professional. As the cost of having a dental professional in schools for reinforcement sessions would be relatively high, the responsibility for these sessions could be delegated to trained school staff, public health workers or parent representatives championing oral health care (Ab Mumin et al, 2021). Having schools take on the added responsibility of reinforcing oral self‐care in adolescents may also be beneficial for those most in need of such behavioural interventions, as our lost‐to‐follow‐up analysis demonstrated that adolescents with worse baseline oral self‐care tended to withdraw from the study.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the oral health promotion facilitator was a dental professional. As the cost of having a dental professional in schools for reinforcement sessions would be relatively high, the responsibility for these sessions could be delegated to trained school staff, public health workers or parent representatives championing oral health care (Ab Mumin et al, 2021). Having schools take on the added responsibility of reinforcing oral self‐care in adolescents may also be beneficial for those most in need of such behavioural interventions, as our lost‐to‐follow‐up analysis demonstrated that adolescents with worse baseline oral self‐care tended to withdraw from the study.…”
Section: Discussionmentioning
confidence: 99%
“…FGD uses open-ended questions to explore the 'how' and 'why' of a particular issue, which then progresses to an in-depth understanding of the context's culture from the study participant's point of view (12,13). The FGD method has been widely used in healthcare studies such as medicine and nursing and, more recently, in dentistry, especially in the use of a guided group discussion format (14). FGD also elicits perceptions, ideas, opinions and thoughts about specific areas of concern, providing rich data from multiple perspectives.…”
Section: Study Design and Settingmentioning
confidence: 99%